Status gizi, kebugaran, kebiasaan sarapan, dan prestasi hafalan santri Roudhotul Qur’an Depok - Desiani Rizki Purwaningtyas; Niken Nurfauziah; Luthfiana Nurkusuma Ningtyas (Jurnal Gizi Klinik Indonesia, 2023)
Nutritional status, physical fitness, breakfast habits, and memorization achievement of students at Roudhotul Qur’an DepokBackground: Memorization is one of the tasks assigned to Islamic boarding school students. However, some pupils find it challenging to memorize and, as a result, have low memorization abilities. Factors influencing memorization performance are nutritional status, physical fitness, and breakfast habits. Objective: The goal of this study was to see if there was a link between students' nutritional status, physical fitness, breakfast routines, and memorizing achievement at Roudhotul Qur'an Islamic Boarding School Depok. Methods: This study uses a cross-sectional research approach—sampling with a technique of sample random sampling. Digital scales, microtoise, Indonesian physical fitness test, food weighing, and students' memorization reports were used to assess nutritional status, physical fitness, breakfast habits, and memorizing achievement. The Chi-Square test was used to analyze the data. Results: The results showed that 71.9% of students had good nutritional status, 88% had sufficient physical fitness, 94.7% ate breakfast with 91.2% sufficient energy contribution, and 68.5% had excellent memorization performance. Data analysis stated there was no relationship between nutritional status (p=0.140) and breakfast habits (p=0,353) with memorization achievement. But, there was a relationship between physical fitness and memorization achievement (p=0.015). Conclusion: Physical fitness is related to memorization achievement at Roudhotul Qur'an Islamic Boarding School Depok.